Serious adverse events and coping strategies of CAR-T cells in the treatment of malignant tumors - Chen, Xiujin; Li, Peng; Tian, Bin; Kang, Xin (Frontiers in Immunology, 2022)
Chimeric antigen receptor T (CAR-T) cells technology has been successfully used in the treatment of B cell-derived hematological tumors and multiple myeloma. Besides, numerous studies of CAR-T cells in solid tumors are also underway. At present, a lot of clinical reports about CAR-T cells in the treatment of malignant tumors have been published. A large number of studies have confirmed the tumor-killing activity of CAR-T cells and confirmed the unique adverse events of CAR-T cells during treatment. Studies have shown that serious adverse events can be life-threatening. Therefore, it is important to pay attention to the serious adverse events of CAR-T cells therapy for its widespread clinical application. In this review, we summarized the serious adverse events of CAR-T cells in the treatment of malignant tumors by reading literature and searching relevant clinical studies. The management and treatment of serious adverse events were discussed. To provide theoretical support for relevant clinicians to manage such patients.